Pengaruh FOMO (Fear of Missing out) By Tiktok Influencer terhadap Minat Beli Produk Scarlett - Cut Tamara Falajunah; Ratih Hendayani (Economic Reviews Journal, 2024)
This study examines the influence of Tiktok influencers on the purchasing interest of Scarlett skincare products in Indonesia. The phenomenon of skincare industry growth and marketing strategies has increased consumer purchasing interest. The research objective is to evaluate the impact of FOMO generated by Tiktok influencers on consumer purchasing interest in Scarlett products. Quantitative methods were employed, collecting data from 350 respondents through surveys, and analyzed using descriptive approaches and structural equation modeling. Findings indicate that social media marketing, particularly through Tiktok influencers, has a significant positive impact on Scarlett product purchasing interest. Materialism also positively and significantly influences purchasing interest, while materialism moderate the relationship between social media marketing and consumer purchase intention. In conclusion, the role of social media and influencers is crucial in influencing consumer behavior in selecting local skincare products in Indonesia.